Tax policy and employment: How does the Swedish system fare? - Jukka Pirttilä; Håkan Selin (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper reviews the literature on optimal taxation of labour income and the empirical work on labour supply and the elasticity of taxable income in Sweden. It also presents an overview of Swedish taxation of labour income, offers calculations on the development in effective marginal tax rates and participation tax rates, and estimates, using the difference-in-differences method, the impact of tax incentives on employment rates of elderly workers. After this background, we ponder possibilities for reforming the Swedish tax system to improve its labour market impacts. We suggest better targeting the earned income tax credit at families and low-income workers, lowering the top marginal tax rates, and maintaining the tax incentives for older workers.
Keywords: H21; H24; J22; 330; optimal taxation; labour income taxation; labour supply; taxable income; Swedish tax system; Lohnsteuer; Optimale Besteuerung; Arbeitsangebot; Ökonomischer Anreiz; Steuersystem; Steuerreform; Beschäftigungseffekt; Schweden